Dendrimers- An Excellent Polymer for Drug Delivery System - Shinde, Madhuri Swamirao.; Bhalerao, Madhuri B.; Thakre, Snehal; Franklin, Jeeja; Jain, Ashish (Asian Journal of Pharmaceutical Research and Development, 2014)
Dendrimers is a type of synthetic polymer. Dendrimer is a novel polymer for various drug delivery systems. A dendrimer is described as a macromolecule, which is characterized by its highly branched 3D structure that provides a high degree of surface functionality and versatility. Dendrimers are monodisperse supramolecule having hyperbranched architecture. As the dendrimers have these properties so it is suitable carrier for drug delivery system. Dendrimers are unimolecular miceller in nature and due to this enhances the solubility of poorly soluble drugs. It has main components i.e. core, branches and end groups. It is also called as cascade molecule. It achieves the controlled and targeted release of drug restricted to the desired area. It has main property of polyvalency i.e presence of many active groups for targeting drug to delivery site. During process of synthesis, properties of dendrimers such as its molecular mass, size, surface group can be controlled and constructed to the desired need. Under this topic we have included what is dendrimer, advantages, properties, factors affecting properties of dendrimers, structure of dendrimers, types of dendrimers, synthesis, characterization of dendrimers. It has various applications for oral, ocular, transdermal, nanodrugs, pulmonary, controlled and targeted drug delivery systems.